2013
DOI: 10.1063/1.4788743
|View full text |Cite
|
Sign up to set email alerts
|

Depth-resolved cathodoluminescence spectroscopy of silicon supersaturated with sulfur

Abstract: We investigate the luminescence of Si supersaturated with S (Si:S) using depth-resolved cathodoluminescence spectroscopy and secondary ion mass spectroscopy as the S concentration is varied over 2 orders of magnitude (10 18 -10 20 cm À3). In single-crystalline supersaturated Si:S, we identify strong luminescence from intra-gap states related to Si self-interstitials and a S-related luminescence at 0.85 eV, both of which show a strong dependence on S concentration in the supersaturated regime. Sufficiently hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…The observed 1/e variation of the sulfur content occurs at the depths of 0.1-0.7 μm for electron energies K, decreasing in the range of 4-10 keV, over the characteristic length δ S ≈ 0.12 μm (Fig. 1c), in good quantitative agreement with previ ous cathode luminescence studies of similar Si sam ples [15]. Importantly, the sulfur content rapidly increases toward the hyperdoped sample surface (by extrapolation to K res in Fig.…”
supporting
confidence: 81%
“…The observed 1/e variation of the sulfur content occurs at the depths of 0.1-0.7 μm for electron energies K, decreasing in the range of 4-10 keV, over the characteristic length δ S ≈ 0.12 μm (Fig. 1c), in good quantitative agreement with previ ous cathode luminescence studies of similar Si sam ples [15]. Importantly, the sulfur content rapidly increases toward the hyperdoped sample surface (by extrapolation to K res in Fig.…”
supporting
confidence: 81%
“…Recently, Fabbri et al . 57 found that S-induced luminescence around 0.85 eV which is at an energy that is deep inside the band gap of a substitutional S atom or a charged S dimer in Si; they also observed that the quenching of luminescence correlated closely with predicted overlap between the impurity band and the conduction band of Si. The VB-PES spectra of S-hyperdoped Si samples herein reveal that the S dopants introduced electron states ~0.7 eV above the E VBM of pure Si, not only forming an impurity band deep inside the band gap of Si that gives rise to strong sub-band gap absorption, but also causing an IMT when the S dopant is at/above a critical concentration 4 5 11 .…”
Section: Resultsmentioning
confidence: 88%
“…3,4,18 In this article, we will focus on the latter concept, which has been studied extensively from a materials standpoint in two primary material systems: silicon hyperdoped with Ti (Si:Ti) [19][20][21][22][23][24][25][26] and silicon hyperdoped with sulfur (Si:S). [27][28][29][30][31][32][33][34][35] Despite significant efforts on these impurity-band materials, no high-efficiency devices have been demonstrated. We present an experimental framework that predicts whether a candidate impurity-band material system will actually enhance the efficiency of a photovoltaic (PV) device.…”
Section: Introductionmentioning
confidence: 99%